O‘QUVCHILARDA KOMMUNIKATIV KO‘NIKMALARNI SHAKLLANTIRISHNING DOLZARB YO‘NALISHLARI - Narziyeva , Mastura Sunnatovna (Educational Research in Universal Sciences, 2023)
Formation of communication skills is important for today. Basically, it is necessary to create an educational environment for students to develop these skills. The article describes the directions for the development of communicative skills.